Fluorescent non-conjugated polymer dots for targeted cell imaging. Issue 18 (27th April 2016) - Sun, Bin; Zhao, Bin; Wang, Dandan; Wang, Yibo; Tang, Qi; Zhu, Shoujun; Yang, Bai; Sun, Hongchen
Abstract : Herein, the new type of non-conjugated polyethyleneimine (PEI) polymer dots (PDs) were further modified by targeting molecules (folic acid). Furthermore, we investigated the targeted bioimaging applications of the PDs in detail, which gave a direction for application of these types of materials. Abstract : Through the chemical crosslinking of the sub-fluorophore, linear non-conjugated polymers can possess strong photoluminescence (PL), which is a very important fluorescence behavior and the non-conjugated polymer dots (PDs) are efficient bio-fluorophores for bio-based applications. Herein, the new type of non-conjugated polyethyleneimine (PEI) PDs was further modified by targeting molecules (folic acid) for a new generation of bio-fluorophores. The free folic acid can quench the PL of PDs by energy transfer, while the conjugated folic acid@PDs (FA@PDs) can still maintain their PL properties to a certain degree. The FA@PDs also possess lower toxicity compared with free PDs, which is possibly due to blocking of the amino groups. Moreover, we investigated the targeted bioimaging applications of the FA@PDs, which gave a very important direction for application of these types of materials.